Imigração italiana na colônia de Antônio Prado - RS: catolicismo e sociabilidades (1885-1945) - Pazuch, Giovane (2015)
The research analyses the sociability among Italian immigrants and their power relations with the Catholic Church and the Brazilian State between 1885 and 1945 in the colony of Antonio Prado in the State of Rio Grande do Sul. From 1885 the Italian immigrants began to cut down the forest in view of occupy the spaces and places of the Colony, where reproduced the villages of Italian origin, with its own architecture. The work aims to identify the conflicts occurring during the formation of a new Italian-Brazilian identity, named ítalo-brasileira, constituted by Catholic religion and Talian as cultural integration language. The Immigrants adapted to the traditions and customs they brought from Italy to Brazil to the new reality lived in the Colony, where they acquired the characteristics of the rural society. The Catholicity and the Italian identity of the Italian immigrants in the Colony formed and developed in Chapel Societies, which gave rise to a society based on family and community values and traditions